rs10732516 polymorphism at the IGF2/H19 locus associates with genotype-specific effects on placental DNA methylation and birth weight of newborns conceived by assisted reproductive technology - Heidi Marjonen (Clinical Epigenetics, 2018)
Abstract Background Assisted reproductive technology (ART) has been associated with low birth weight of fresh embryo transfer (FRESH) derived and increased birth weight of frozen embryo transfer (FET)-derived newborns. Owing to that, we focused on imprinted insulin-like growth factor 2 (IGF2)/H19 locus known to be important for normal growth. This locus is regulated by H19 imprinting control region (ICR) with seven binding sites for the methylation-sensitive zinc finger regulatory protein (CTCF). A polymorphism rs10732516 G/A in the sixth binding site for CTCF, associates with a genotype-specific trend to the DNA methylation. Due to this association, 62 couples with singleton pregnancies derived from FRESH (44 IVF/18 ICSI), 24 couples from FET (15 IVF/9 ICSI), and 157 couples with spontaneously conceived pregnancies as controls were recruited in Finland and Estonia for genotype-specific examination. DNA methylation levels at the H19 ICR, H19 DMR, and long interspersed nuclear elements in placental tissue were explored by MassARRAY EpiTYPER (n = 122). Allele-specific changes in the methylation level of H19 ICR in placental tissue (n = 26) and white blood cells (WBC, n = 8) were examined by bisulfite sequencing. Newborns’ (n = 243) anthropometrics was analyzed by using international growth standards. Results A consistent trend of genotype-specific decreased methylation level was observed in paternal allele of rs10732516 paternal A/maternal G genotype, but not in paternal G/maternal A genotype, at H19 ICR in ART placentas. This hypomethylation was not detected in WBCs. Also genotype-specific differences in FRESH-derived newborns’ birth weight and head circumference were observed (P = 0.04, P = 0.004, respectively): FRESH-derived newborns with G/G genotype were heavier (P = 0.04) and had larger head circumference (P = 0.002) compared to newborns with A/A genotype. Also, the placental weight and birth weight of controls, FRESH- and FET-derived newborns differed significantly in rs10732516 A/A genotype (P = 0.024, P = 0.006, respectively): the placentas and newborns of FET-derived pregnancies were heavier compared to FRESH-derived pregnancies (P = 0.02, P = 0.004, respectively). Conclusions The observed DNA methylation changes together with the phenotypic findings suggest that rs10732516 polymorphism associates with the effects of ART in a parent-of-origin manner. Therefore, this polymorphism should be considered when the effects of environmental factors on embryonic development are studied.